(untitled) (Research, Society and Development, 2020)
The Administrative Improbity Law represents a milestone in Brazilian legislation with regard to combating corruption. By establishing limits on the role of public agents, a Law sanctions conduct that undermines the treasury and the principles of Public Administration. However, after two decades in force, the application of this standard still permeates dialogues in the field of legal science. Thus, this article aims to conduct a systematic literature review in order to investigate the scientific production of articles dealing with this matter. It is understood that this review will allow the identification of existing gaps, thus guiding future studies on the topic. The database chosen was the CAPES Periodical where 11 studies were selected. When analyzing the results, it is possible to notice a large time lag between the law and the publication of the researched articles. This shows that, despite 28 years in force, the Improbity Law continues to be the subject of discussion. There was an inevitable association between research and corrupt conduct and administrative improbity in conduct offensive to the environment. Another highlight is the use of qualitative methodology, by most researchers.